Stable chlorine isotope analysis of triclosan using GC-qMS: Method development and applications. (June 2021) - Liu, Yi; Liu, Shiyang; Wang, Qiang; Gligorovski, Sasho; Zhang, Gan; Jin, Biao
Abstract: Occurrence of triclosan (TCS) in water environment caused a serious concern due to TCS toxic properties as well as yield of toxic byproducts during natural attenuation. Here we developed an online approach for chlorine compound specific isotope analysis (CSIA) of TCS based on gas chromatography quadrupole mass spectrometry (GC-qMS). Specifically, the instrumental parameters including dwell time, ionization energy and split ratio values were tested and optimized. Moreover, the calculation scheme considering all the TCS molecular ions presented better precision compared with the method using the most abundant neighboring ion pairs. The optimized method was validated by applying it to differentiate various TCS manufacturers, and was used to resolve chlorine isotope fractionation occurring during TCS photodegradation induced by simulated solar radiation. Chlorine isotopic enrichment factor ( ε C l ) of −2.61 ± 0.37‰ and −0.72 ± 1.95‰ were obtained at pH values of 8.3 and 4.5, respectively. This indicates that preferential cleavage of C-Cl bonds occurred at a higher pH value. Thus, this study provides a robust and sensitive approach for chlorine CSIA of TCS, and could be readily applied to monitor chlorine isotope effects during TCS environmental transformations. Graphical abstract: Image 1 Highlights: An efficient approach for chlorine CSIA of triclosan using GC-qMS. Fingerprinting different sources of synthetic triclosan. Tracking bond-cleavage transformation pathways of triclosan.